2013
DOI: 10.1515/ijnes-2012-0009
|View full text |Cite
|
Sign up to set email alerts
|

High Fidelity Simulation Effectiveness in Nursing Students’ Transfer of Learning

Abstract: Transfer of learning was demonstrated and the use of HFS was found to be an effective learning and teaching method. Implications of results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 14 publications
2
39
0
3
Order By: Relevance
“…A growing body of literature provides evidence that high fidelity simulation improves knowledge acquisition and critical thinking of undergraduate nursing students, [20] as well as self-efficacy and learner satisfaction, [21][22][23] and that the knowledge and skills gained from simulation practice transfers directly to the point of care. [22,24,25] Consistent with the literature, students in accelerated baccalaureate programs engaged in high fidelity simulation report learner satisfaction and increased self-efficacy and competence for clinical practice. [26,27] A key challenge in the integration and use of high fidelity simulation in nursing curricula is the measurement and evaluation of clinical competencies.…”
Section: Introductionsupporting
confidence: 53%
“…A growing body of literature provides evidence that high fidelity simulation improves knowledge acquisition and critical thinking of undergraduate nursing students, [20] as well as self-efficacy and learner satisfaction, [21][22][23] and that the knowledge and skills gained from simulation practice transfers directly to the point of care. [22,24,25] Consistent with the literature, students in accelerated baccalaureate programs engaged in high fidelity simulation report learner satisfaction and increased self-efficacy and competence for clinical practice. [26,27] A key challenge in the integration and use of high fidelity simulation in nursing curricula is the measurement and evaluation of clinical competencies.…”
Section: Introductionsupporting
confidence: 53%
“…There is a need for other ways of exploring the impact of simulation training, particularly as research indicates that students appear to lack capability to judge their own performance, [20] and facilitators tend to be too subjective in their evaluations. [17] A review of the literature identified two studies [21,22] that directly reported on students' skill performance across skills centre and clinical setting. Alteren & Bjørk [21] investigated if role-play as a learning strategy influenced the skill of helping the patient to eat and drink.…”
Section: Simulation-based Learningmentioning
confidence: 99%
“…Students experienced different but complementary learning opportunities in the two learning environments, and similarities between the two learning settings supported their performance. Kirkman [22] explored how high-fidelity simulation prepared nursing students to perform a respiratory assessment on actual patients. High-fidelity simulation was an effective learning strategy, and students applied what was achieved in the simulation session to actual patients.…”
Section: Simulation-based Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] A study of 42 students using high-fidelity simulation involving a respiratory care scenario demonstrated transfer of learning to application. [22] However, other literature finds that the transfer of learning outcomes is unaffected by the fidelity of simulation. [23] 2.…”
Section: Simulationmentioning
confidence: 99%